Value chain school with climate change and gender perspective: Learning and monitoring guide. - International Potato Center (International Potato Center, 2019)
The value chain school (VCS) is a participatory action learning process that involves farmer groups participating in agricultural value chains. As part of capacity strengthening, VCS comprises a series of group‐based experiential learning activities over a production‐marketing cycle while interacting with other chain actors and stakeholders. As a tangible outcome of VCS, the farmer‐participants are expected to have initiated or strengthened a business upon completing the VCS learning process. VCS aspires to more profitable pro‐poor farm business through market‐oriented innovations that enhance trust, coordination, and collaboration between farmers and other chain actors while empowering men and women farmers, thus ultimately contributing to sustainable livelihoods of targeted farming households.